Nursing students' perceptions of support and active learning regarding simulation-based education in Lesotho: A quantitative study - P S Moabi; N G mtshali (South African Medical Association, 2022)
Background. Simulation has taken centre stage in health sciences education in the context of the increasing adoption of a competency-based curriculum. Simulation replicates facets of the real world in an interactive manner that allows students to learn clinical skills and develop clinical reasoning skills in a safe learning environment. Facilitators have a responsibility to provide adequate instructional and psychological support to the students, while facilitating active and self-directed learning in the simulation environment. Objective. To explore and describe students' perceptions of support and active learning regarding simulation-based education (SBE) in Lesotho. Methods. A quantitative descriptive exploratory study was conducted using a validated questionnaire. A total of 275 nursing students participated in the study. A stratified systematic random sampling method was used and data were analysed using SPSS version 27. Results. The majority of participants (87.9%) had a positive perception of support that was offered prior, during and after simulation, which they appreciated. Active learning was also perceived positively, as most of the participants indicated that they actively participated in, and not merely observed, simulation. The results showed significant associations between an opportunity given to students to discuss simulation objectives with the teacher and various institutions (p<0.05 (p=0.01)). Institutions with trained simulation facilitators provided students the opportunity to discuss simulation objectives with their teacher. Conclusion. The study showed that student support and active learning are essential when conducting SBE. Supporting students and actively involving them in the learning process lead to effective learning.